ACVIM consensus statement on diagnosis and management of acute canine thoracolumbar intervertebral disc extrusion. (25th July 2022) - Olby, Natasha J.; Moore, Sarah A.; Brisson, Brigitte; Fenn, Joe; Flegel, Thomas; Kortz, Gregg; Lewis, Melissa; Tipold, Andrea
Abstract: Background: Thoracolumbar intervertebral disc extrusion (TL‐IVDE) is the most common cause of acute paraparesis and paraplegia in dogs; however, guidelines on management of the condition are lacking. Objectives: To summarize the current literature as it relates to diagnosis and management of acute TL‐IVDE in dogs, and to formulate clinically relevant evidence‐based recommendations. Animals: None. Methods: A panel of 8 experts was convened to assess and summarize evidence from the peer‐reviewed literature in order to develop consensus clinical recommendations. Level of evidence available to support each recommendation was assessed and reported. Results: The majority of available literature described observational studies. Most recommendations made by the panel were supported by a low or moderate level of evidence, and several areas of high need for further study were identified. These include better understanding of the ideal timing for surgical decompression, expected surgical vs medical outcomes for more mildly affected dogs, impact of durotomy on locomotor outcome and development of progressive myelomalacia, and refining of postoperative care, and genetic and preventative care studies. Conclusions and Clinical Importance: Future efforts should build on current recommendations by conducting prospective studies and randomized controlled trials, where possible, to address identified gaps in knowledge and to develop cost effectiveness and number needed to treat studies supporting various aspects of diagnosis and treatment of TL‐IVDE.